2021
DOI: 10.1101/2021.07.12.451842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low lamin A levels enhance confined cell migration and metastatic capacity in breast cancer

Abstract: Aberrations in nuclear size and shape are commonly used to identify cancerous tissue. However, it remains unclear whether the disturbed nuclear structure directly contributes to the cancer pathology or is merely a consequence of other events occurring during tumorigenesis. Here, we show that highly invasive and proliferative breast cancer cells have lower expression of the nuclear envelope proteins lamin A/C, leading to increased nuclear deformability that permits enhanced cell migration through confined envir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 185 publications
(254 reference statements)
1
9
0
Order By: Relevance
“…A previous study found that overexpression of Akt resulted in a more than 4-fold increase of lamin A in interphase cells, but a 50% decrease in lamin A expression in mitotic cells ( Bertacchini et al, 2013 ). In recent experiments with MDA-MB-231 cells, we found that Akt inhibition resulted in a significant increase in lamin A/C protein levels, without changing LMNA gene expression ( Bell et al, 2021 ). Thus, it remains to be investigated if and how Akt may mediate effects of ATM inhibition on lamin A/C protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that overexpression of Akt resulted in a more than 4-fold increase of lamin A in interphase cells, but a 50% decrease in lamin A expression in mitotic cells ( Bertacchini et al, 2013 ). In recent experiments with MDA-MB-231 cells, we found that Akt inhibition resulted in a significant increase in lamin A/C protein levels, without changing LMNA gene expression ( Bell et al, 2021 ). Thus, it remains to be investigated if and how Akt may mediate effects of ATM inhibition on lamin A/C protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] Lamin A/C, and not lamin B1, limits the passage of the nucleus through confining pores in 3D collagen gels or microfabricated microchannels. [ 19 , 20 ] Furthermore, the depletion of lamin A/C but not lamin B1 significantly softens the nucleus. [ 21 ] These studies collectively suggest that the mechanical stiffness conferred onto the nucleus by lamin A/C impedes nuclear deformation and hence cell passage through narrow micropores or channels.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence implicates LMNA/C in preserving nuclear integrity in ovarian epithelial cancer subtypes [ 88 ] and non-small-cell lung carcinoma cells [ 79 ]. Accordingly, lower LMNA/C levels in invasive breast cancer cells confer increased nuclear deformations enabling enhanced cell invasiveness [ 89 ]. Recent implications of LMNA/C in the p53/p16 INK4A senescence pathway [ 80 ] suggest an interplay between chromatin and signaling functions modulated by A-type lamins which will be worth investigating more closely.…”
Section: Discussionmentioning
confidence: 99%